Impact of Inclusion of Multicomponent Synbiotic Russian Holstein Dairy Cow's Rations on Milk Yield, Rumen Fermentation, and Some Blood Biochemical Parameters - Trukhachev, Vladimir I.; Buryakov, Nikolai P.; Shapovalov, Sergey O.; Shvydkov, Aleksandr N.; Buryakova, Maria A.; Khardik, Irina V.; Fathala, Mohamed M.; Komarova, Oksana E.; Aleshin, Dmitrii E. (Frontiers in Veterinary Science, 2022)
The purpose of this study was to appraise the effect of inclusion of ‎multicomponent symbiotic ‎‎"Kormomix® Rumin" in feeding lactating ‎Holstein cows on milk productivity, indicators of rumen fermentation ‎metabolism and some hematological and biochemical parameters of ‎blood. forty highly productive Russian Holstein cows were selected ‎according to their productivity, physiological condition, live weight and ‎age. They were divided into four groups (10 heads/ each). All animals ‎received the basal total mixed ration (TMR), which was balanced and ‎corresponded to the nutritional requirements for cows during the milking ‎period with a milk yield of 36 kg of milk/ daily. First group served as ‎control and fed basal TMR while the 2nd and the 3rd and the 4th group fed ‎the basal TMR supplemented with a multicomponent symbiotic ‎‎"Kormomix® Rumin" in amounts (25, 50 and 75 g/head/day) respectively ‎which was administered manually and individually directly after calving ‎and until 120 DIM. Milk, ruminal juice and blood samples were ‎collected. The introduction of 25 g / head / day of "Kormomix® Rumin" ‎recorded the highest values in all studied parameters of milk. The use of ‎a multicomponent symbiotic "Kormomix® Rumin" reflected in an ‎optimization of rumen fermentation, it stimulated a significant increase ‎in the synthesis of volatile fatty acids in the 2nd experimental group (9.38 ‎vs. 7.04 mmol /100 ml). The pH level recorded from (6.87 to 6.99 ‎against 7.10) in the control group. ‎The level of ammonia in the rumen ‎due to the proteolytic activity of the feed additive increased in the 2nd, 3rd ‎and 4th experimental groups when compared with control group. The ‎level of α-Amylase (total) decreased significantly in the 2nd experimental ‎group when compared with other groups. The ratio of Urea/Creatinine ‎recorded the lowest value in the 4th group and the difference was ‎significant when compared with the 2nd group. Consequently, the ‎inclusion of multicomponent symbiotic "Kormomix® Rumin" in the diet ‎of lactating cows has a stimulatory effect on increasing the milk ‎production by improving the intensity of rumen fermentation which, ‎contributes to more efficient utilization of feed without any harmful ‎effects on blood traits.‎‎